Implementation of IMDCT Block of an MP3 Decoder through Optimization on the DCT Matrix - Galabov, Miroslav (Radioengineering Society, 2004)
The paper describes an attempt to create an efficient dedicated MP3-decoder, according to the MPEG-1 Layer III standard. A new method of Inverse Modified Discrete Cosine Transform by optimization on the Discrete Cosine Transform (DCT) matrix is proposed and an assembler program for Digital Signal Processor is developed. In addition, a program to calculate DCT using Lee's algorithm for any matrix of the size 2M is created. The experimental results have proven that the decoder is able to stream and decode MP3 in real time.
Keywords: IMDCT; MP3 decoder; bitstream; DSP